The Impact of Computers on the Writing Processes of First-Grade Students - Thigpen, Andrea K. (Valdosta State University, 2003)
The purpose of the research was to determine the impact of computers on the quality and quantity of student writing, the number of revisions made by the students, and the attitudes of the students toward writing. Before beginning the action research study, a literature review was conducted in order to see what research has already been conducted in the area of computers as writing tools. The instructional unit was taught over a fourweek time span. The participants in this study were forty-three first-grade students. This study included an evaluation of writing samples, teacher observation, and a postintervention student survey. As the students learned the steps of the writing process, they worked with a partner to write a story. The students in the control group wrote with paper and pencil, while the students in the experimental group wrote on the computer. Findings suggest that the students who wrote on the computer wrote better quality stories, wrote longer stories, made more revisions, and had a better overall attitude toward writing.
Keywords: Student writing; Computers; Quality; Educational technology; Teaching--Aids and devices; Computer-assisted instruction